Traditional herbal medicine for anorexia in patients with cancer: a systematic review and meta-analysis of randomized controlled trials - Park, Su Bin; Yoon, Jee-Hyun; Kim, Eun Hye; Jin, Hayun; Yoon, Seong Woo (Frontiers in Pharmacology, 2023)
Background: The purpose of this systematic review and meta-analysis was to evaluate the efficacy and safety of traditional herbal medicine (THM) for improving anorexia in patients with cancer. Methods: We searched for randomized controlled trials (RCTs) that evaluated orally administered THM for cancer-related anorexia using 10 databases from the inception to August 1, 2021. The primary outcome was an improvement in anorexia, measured with the total effective rate (TER) or visual analog scale (VAS). The secondary outcomes were the changes in body weight, the Karnofsky performance scale, acylated ghrelin, and adverse events. We used the Cochrane risk of bias assessment tool and the Grading of Recommendations Assessment, Development, and Evaluation method to assess the quality of the studies and the quality of the evidence. Results: A total of 26 RCTs were included, of which 23 were subjected to quantitative analysis. THM showed a significant improvement in anorexia measured with the TER (risk ratio [RR] 1.12, 95% confidence intervals [CI] 1.04 to 1.20) than appetite stimulants with moderate quality evidence and in the Karnofsky performance scale (RR 1.38, 95% CI 1.12 to 1.70) with low quality evidence but not in body weight gain (RR 0.98, 95% CI 0.80 to 1.20). THM showed a significant improvement in anorexia measured with the TER (RR 1.74, 95% CI 1.23 to 2.48) compared with usual care with low-quality evidence but did not significantly improve the VAS score (mean difference 0.72, 95% CI 0.00 to 1.43) or the level of acylated ghrelin (mean difference 0.94, 95% CI 1.08 to 2.97). There were no serious adverse events.This review suggests that THM may be considered a safe alternative therapeutic option for improving anorexia in patients with cancer. Nonetheless, more rigorous RCTs are needed due to methodological limitations.